2006
DOI: 10.1152/ajpregu.00896.2005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term facilitation of ventilation and genioglossus muscle activity is evident in the presence of elevated levels of carbon dioxide in awake humans

Abstract: We hypothesized that long-term facilitation (LTF) of minute ventilation and peak genioglossus muscle activity manifests itself in awake healthy humans when carbon dioxide is sustained at elevated levels. Eleven subjects completed two trials. During trial 1, baseline carbon dioxide levels were maintained during and after exposure to eight 4-min episodes of hypoxia. During trial 2, carbon dioxide was sustained 5 mmHg above baseline levels during exposure to episodic hypoxia. Seven subjects were exposed to sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
148
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(179 citation statements)
references
References 50 publications
21
148
7
Order By: Relevance
“…The occurrence of GG LTF in sleeping humans is in contrast to studies during wakefulness that have shown no evidence of GG LTF (McEvoy et al 1996, Jordan et al 2002, unless episodic hypoxia was accompanied by hypercapnia (Harris et al 2006). The discrepancy between wakefulness and NREM sleep vis-à-vis GG LTF could be attributed to higher upper airway resistance during sleep, augmenting negative supraglottic pressure and the magnitude of GG activation.…”
Section: Ltf Of Genioglossusmentioning
confidence: 75%
See 1 more Smart Citation
“…The occurrence of GG LTF in sleeping humans is in contrast to studies during wakefulness that have shown no evidence of GG LTF (McEvoy et al 1996, Jordan et al 2002, unless episodic hypoxia was accompanied by hypercapnia (Harris et al 2006). The discrepancy between wakefulness and NREM sleep vis-à-vis GG LTF could be attributed to higher upper airway resistance during sleep, augmenting negative supraglottic pressure and the magnitude of GG activation.…”
Section: Ltf Of Genioglossusmentioning
confidence: 75%
“…Experimental conditions also influence the development of LTF. An example is the occurrence of LTF following episodic hypoxia in awake human subjects, only in the presence of concomitant hypercapnia (Harris et al 2006). Finally, LTF may manifest differently across different motor nuclei, manifesting in the phrenic motorneuron (Fuller et al 2000) or hypoglossal motorneuron (Bach and Mitchell, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This, along with the potential stress associated with contention, may contribute to prevent ventilatory LTF. Finally, ventilatory LTF expression in adult rats is larger under iso-and hypercapnic conditions (18,45). Because our experiments were done under poikilocapnic hypoxia, this may further limit LTF.…”
Section: Methodological Considerationsmentioning
confidence: 95%
“…IH protocol (eight 4-min periods of hypoxia (inspiratory oxygen fraction (FIO 2 ) 8%), separated by 5 min of normoxia (FIO 2 21%)) describe an increase in both tidal volume and breathing frequency [37,38]. Thus, findings regarding the ventilatory pattern of IH-induced LTF is equivocal, and probably the result of varying IH protocols.…”
Section: Resting Ventilationmentioning
confidence: 99%